Development of Canva-Based Interactive Learning Media to Improve Students’ Understanding in the Islamic Religious Education Subject at Integrated Islamic Elementary School Darul Falah Kertosono Nganjuk - M. Khoirul Anam Catur Pamungkas (PGMI, STAI Miftahul Ula Nganjuk, 2025)
The development of **interactive learning multimedia using the Canva application for Grade III at Integrated Islamic Elementary School Darul Falah Kertosono, Nganjuk** is based on the phenomenon observed in the school, namely the suboptimal use of learning media. This condition occurs because teaching practices tend to focus more on classroom management, and the learning process is still limited to the use of student worksheets (LKS) as learning media. The objectives of this study are: (1) to describe the development of interactive learning multimedia using the Canva application for the material *The Story of Prophet Ibrahim* for Grade III students; and (2) to describe the results of the trial of the interactive learning media using the Canva application for the material *The Story of Prophet Ibrahim* for Grade III at Integrated Islamic Elementary School Darul Falah Kertosono, Nganjuk, in the 2023/2024 academic year. The research method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a Research and Development (R&D) design. The researcher focuses on developing Canva-based media to meet students’ needs. Data collection techniques include observation, interviews, and questionnaires, while the data analysis used is descriptive qualitative. The research subjects consisted of 12 students. The results of the study generally show that the media expert validation score reached 93%, the material expert validation score reached 94%, student responses to the media reached 95%, the trial results reached 98% with a very good qualification—indicating that students understood the material and were able to use the media—and the classroom teacher’s response to the media reached 98%. Thus, the interactive learning multimedia using the Canva application is considered very feasible to be used as a learning medium.